1976
DOI: 10.1002/cpt197619118
|View full text |Cite
|
Sign up to set email alerts
|

Assay of aspirin and naproxen analgesia

Abstract: To establish the relative potency of naproxen and aspirin for oral analgesia, a 4-point, noncrossover bioassay with placebo control was undertaken with 197 patients. Subjective-response methods were used to determine two measures of postoperative analgesia over a period of 6 hr. With reasonable confidence for an oral analgesic assay, we found 220 mg of naproxen to be equivalent to 600 mg of aspirin for pain relief and 330 mg of naproxen to be equivalent to 600 mg of aspirin for decreased pain intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…There were 17 citations [14–30] with relevant direct comparisons (18 trials) of more than one dose of aspirin. There were four comparisons of 500 and 1000 mg and 10 of 600 or 650 g and 1000 or 1200 mg. Other comparisons included doses of 200, 300, 325, 625, 650, 750 and 900 mg.…”
Section: Resultsmentioning
confidence: 99%
“…There were 17 citations [14–30] with relevant direct comparisons (18 trials) of more than one dose of aspirin. There were four comparisons of 500 and 1000 mg and 10 of 600 or 650 g and 1000 or 1200 mg. Other comparisons included doses of 200, 300, 325, 625, 650, 750 and 900 mg.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with single 200 to 600 mg doses of naproxen have shown it to be at least as effective as single standard doses of aspirin or other standard reference analgesics in patients with moderate or severe postoperative pain resulting from orthopaedic (Ruedy & McCullough, 1973), dental (Ruedy, 1973), and other surgical procedures (Mahler, Forrest, Brown, Shroff, Gordon, Brown & James, 1976;Stetson, Robinson, Wardell & Lasagna, 1973). The need for an analgesic agent with an even faster onset of action than naproxen, however, has led to an investigation of methods to increase the speed of absorption of naproxen.…”
Section: Introductionmentioning
confidence: 99%
“…It is used in the treatment of adult osteo and rheumatoid arthritis [1, 2] as well as for the relief of fever [3] and moderate pain [4,5], including pain associated with dysmenorrhea [6]. Although the drug is marketed for adult use in the United States, experience in children is limited [3,7], This study was designed to develop experience regarding metabolism and excretion of the drug, to derive dosage recommendations appropriate for pediatric pa tients.…”
mentioning
confidence: 99%